High Prevalence of Headaches During Covid‐19 Infection: A Retrospective Cohort Study. Issue 10 (5th August 2020) - Poncet‐Megemont, Louis; Paris, Pauline; Tronchere, Amélie; Salazard, Jean‐Pascal; Pereira, Bruno; Dallel, Radhouane; Aumeran, Claire; Beytout, Jean; Jacomet, Christine; Laurichesse, Henri; Lesens, Olivier; Mrozek, Natacha; et al.
Abstract : Objectives: To document the prevalence of new headaches in patients with Covid‐19 infection and the potential association with other neuro‐sensorial symptoms (anosmia and ageusia). The persistence of these symptoms 1 month after recovery was also documented. Background: Headaches are a very common symptom of viral infections. Surprisingly, early Chinese studies reported a relatively low prevalence (12‐15%) of headaches associated with Covid‐19. Methods: All the patients with laboratory‐confirmed or chest‐CT‐confirmed Covid‐19 infection, diagnosed between February 27 th and April 15 th, 2020 in the dedicated laboratory of Clermont‐Ferrand University Hospital were followed for 1 month after recovery. Results: A total of 139 consecutive patients (mean [SD] age, 48.5 [15.3] years; 87 women [62.6%]) were interviewed 1 month after disappearance of fever and dyspnea (semi‐structured phone interview). Overall, 59.0% (82/139) of people with Covid‐19 had mild disease, 36.7% (51/139) had severe disease, and 4.3% (6/139) had critical illness. Eighty‐two (59.0%; 95% CI: 50.3 to 67.3) reported new headaches during the acute phase and 3.6% (5/139) had persistent headaches 1 month after fever and dyspnea remission. Anosmia and ageusia were also very common, occurring in 60.4% (84/139) and 58.3% (81/139) of the patients, respectively. These 2 symptoms persisted in 14.4% (20/139) and 11.5% (16/139) of Covid‐19 patients 1 month after recovery. Headaches were neither clearly associated with anosmia, nor with ageusia, and were not associated with disease severity (ie, requiring hospitalization or intensive care unit). Conclusion: This specific study highlights the high prevalence of new headaches during Covid‐19 infection in French patients. Further studies are needed to refine the characterization of patients with Covid‐19‐associated headaches.